Determinasi Usia Ibu, Paritas, dan Kekurangan Energi Kronis Terhadap Risiko Bayi Berat Badan Lahir Rendah - Feliciani Palmita Sari Harapan; Adelbertha A. Berkanis (Jurnal Ners, 2025)
Background: Low birth weight (LBW) remains a significant public health problem that increases child mortality and morbidity rates, accounting for 40–60% of neonatal deaths worldwide. Maternal factors such as advanced maternal age, poor nutritional status (chronic energy deficiency), anemia, and high parity are proven contributors to LBW. Case studied : A term baby girl was delivered spontaneously in the hospital to a 45-year-old mother with a history of grand multiparity, chronic energy deficiency (KEK), and mild anemia. The mother had limited access to antenatal care and did not consistently take prenatal vitamins during pregnancy. The infant’s birth weight was 2100 grams Within the first hour of life, the baby successfully initiated early breastfeeding (IMD). Continuous monitoring of the infant’s general condition and vital signs was performed, and the midwife provided counseling on the importance of exclusive breastfeeding. The babys mother also received comprehensive postpartum care, including routine monitoring, health education on personal hygiene, counseling on postpartum contraception, as well as emotional and psychosocial support to promote maternal well-being and strengthen family involvement in newborn care. Conclusion: This case highlights that advanced maternal age, poor nutritional status, and high parity significantly contribute to the occurrence of LBW. Comprehensive care—including immediate postnatal interventions, continuous monitoring, nutritional education, psychosocial support, and active family involvement is essential in preventing complications and promoting the long-term health of both mother and child.